Exaggeration in Contemporary Art as an Emphasis Tool of Artistic Expression: A Descriptive Analytical Study - Al-Nahari , Nourah Nasser (Dirasat: Human and Social Sciences, 2023)
Objectives: The research aims to identify the most critical methods in which exaggeration is used in contemporary artworks and verify its role as an emphasis tool for artistic expression in contemporary arts. Methods: The survey was conducted using a descriptive-analytical approach. With a random sample of (319) respondents, the study society included artists, art students, and audience who attended the Dir'iyah Biennale in Riyadh (2021-2022 AD). Results were gathered by using a questionnaire tool to address the following research questions: what are the most important ways to use exaggeration in contemporary artworks, and what role does exaggeration play as an emphasis tool for artistic expression? Results: Based on the findings, exaggeration plays a key role in emphasizing and enriching artistic expression, since exaggeration attracts one's attention and evokes thought regarding content and meaning. Additionally, exaggeration can help the artist convey emotions. The majority of respondents agreed with the artists' use of exaggeration in contemporary artworks; accordingly, the most important methods of exaggeration from their point of view are: (exaggeration in: details, color, shape, size, elements, and space, respectively); Moreover, they agreed that exaggeration has a role to play in contemporary art as tool of affirmation of artistic expression in contemporary arts. Conclusion: Exaggeration opens rooms of discussing artwork with others about its meaning, draws attention to different meanings from the usual in artwork, allows a wide space for interaction with artwork as well, and gives a new understanding of contemporary art.